TREND MOMENT METHOD IN PREDICTING THE NUMBER OF SALES OF MATIC MOTORCYCLES - Febby Madonna Yuma (STMIK Royal, 2022)
Abstract: PT. Panca Niaga Mandiri is an authorized motorcycle dealer in Sei Piring which is engaged in selling Honda motorcycles both in cash and on credit. Dealer Problems PT. Tunas Dwipa Putra at this time is that there is no definite calculation to predict the motorcycle sales target each month and the problems that occur are that sometimes there is an increase or decrease in motorcycle sales for each month because currently, business competition is very tight so that it makes business people compete with each other in their way. Many strategies have been carried out by marketing for how monthly motorcycle sales continue to increase. Therefore, it is necessary to use a forecasting method to predict sales of Honda motorcycles, especially automatic-type Honda motorcycles. The method used is the Trend Moment method. It is hoped that this method can help predict sales of automatic motorcycles for the next month.Keywords: honda motorcycle; prediction; sales; Abstrak: PT. Panca Niaga Mandiri merupakan dealer resmi sepeda motor yang ada di Sei Piring yang bergerak pada penjualan sepeda motor honda baik secara tunai maupun secara kredit. Permasalahan Dealer PT. Tunas Dwipa Putra pada saat ini yaitu tidak adanya perhitungan yang pasti untuk memprediksi target penjualan motor disetiap bulannya dan permasalahan yang terjadi terkadang mengalami kenaikan maupun penurunan penjualan sepeda motor untuk setiap bulannya, Karena saat ini persaingan bisnis sangat ketat sekali sehingga membuat para pelaku bisnis saling bersaing dengan cara mereka sendiri. Banyak strategi yang sudah dilakukan oleh marketing untuk bagaimana penjualan sepeda motor setiap bulanya terus meningkat. Oleh karena itu, maka diperlukan metode peramalan untuk memprediksi penjualan sepeda motor honda khususnya sepeda motor honda type matic. Metode yang digunakan yaitu metode Trend Moment diharapakan metode ini dapat membantu dalam memprediksi penjualan sepeda motor matic untuk bulan kedepannya. Kata kunci:penjualan; prediksi;sepeda motor honda